PENICILLIN RESISTANCE OF COMPETENT CELLS IN DEOXYRIBONUCLEIC ACID TRANSFORMATION OF BACILLUS SUBTILIS - Nester, E. W. (1964)
Nester, E. W. (University of Washington, Seattle). Penicillin resistance of competent cells in deoxyribonucleic acid transformation of Bacillus subtilis. J. Bacteriol. 87:867–875. 1964.—Transformants are resistant to penicillin killing for several hours after deoxyribonucleic acid (DNA) addition. The present study indicates that this resistance is a consequence of such cells still remaining competent and is not the result of any interaction of donor DNA with the recipient cell. The following data support this conclusion: (i) the frequency of transformation can be increased five- to tenfold if penicillin acts on a competent culture prior to DNA addition; (ii) the percentage of competent cells in such a penicillin-treated culture calculated on the basis of a random coincidence of DNA molecules entering the same cell increases some 25-fold over that of a penicillin-nontreated population; (iii) the kinetics of penicillin killing of a recipient culture are identical whether or not transforming DNA has been added; (iv) the extent of killing by penicillin is related to the level of competence of the recipient culture; and (v) the kinetics of appearance and disappearance of competence in a population as well as in individual cells indicate that a cell may remain competent for 3 to 4 hr.